2021
DOI: 10.3390/ma14237290
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Hazard Evaluation of Some Egyptian Magmatic Rocks Used as Ornamental Stone: Petrography and Natural Radioactivity

Abstract: Magmatic rocks represent one of the most significant rocks due to their abundance, durability and appearance; they can be used as ornamental stones in the construction of dwellings. The current study is concerned with the detailed petrography and natural radioactivity of seven magmatic rocks. All are commercial granitic rocks and are identified as black Aswan, Nero Aswan, white Halayeb, Karnak, Verdi, red Hurghada and red Aswan. Their respective mineralogical compositions are classified as porpheritic granodio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Geologically, Egyptian granitic intrusions are widely distributed in the northern sector of the Eastern Desert, which represents the western part of the Arabian Nubian Shield (ANS). These rocks are of different ages and mineralogical and geochemical compositions; furthermore, they are also of different tectonic regimes, ranging from Syn-orogenic (older rocks, 850–610 Ma) to late post-orogenic (younger rocks, 610–550 Ma) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geologically, Egyptian granitic intrusions are widely distributed in the northern sector of the Eastern Desert, which represents the western part of the Arabian Nubian Shield (ANS). These rocks are of different ages and mineralogical and geochemical compositions; furthermore, they are also of different tectonic regimes, ranging from Syn-orogenic (older rocks, 850–610 Ma) to late post-orogenic (younger rocks, 610–550 Ma) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lasheen et al [ 7 ] studied the relationship between the natural radioactivity of some commercial granitic rocks and their petrographical description, including mineralogical constitutions. They found that the rock types with a lack of accessory minerals such as allanite, monazite, titanite, thorite, and zircon yielded low activity concentrations of natural radioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Granitic rocks represent the most abundant plutonic rocks in the continental crust [1]. Their distribution in Arabian-Nubian Shield (ANS) is heterogeneous, since they are abundant in the northern ANS [2][3][4][5][6]. Granitic rocks cover about sixty percent of the Egyptian crystalline rocks in the Eastern Desert, which decreases to thirty percent in the south (Kenya and Ethiopia) of ANS [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Granitic rocks cover about sixty percent of the Egyptian crystalline rocks in the Eastern Desert, which decreases to thirty percent in the south (Kenya and Ethiopia) of ANS [7,8]. Field, petrological, geochemical, and isotopic studies discriminate the Egyptian granitic rocks into older (850-610 Ma) and younger granites (610-550 Ma) [2,8]. The former (older) include calc-alkaline tonalite-granodiorite association (gray) of syn-orogenic rocks with I-type signature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation